2015
DOI: 10.1007/s00381-015-2941-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of pediatric single-level vertebral hemangiomas presenting with myelopathy by three-pronged approach (ethanol embolization, laminectomy, and instrumentation): a single-institute experience

Abstract: The present study is the largest series of pediatric symptomatic VH. This procedure is a safe, efficient method to treat symptomatic pediatric VH with severe cord compression. It seems to serve the purpose of providing embolization, cord decompression, rigid fusion at the same sitting without adding new morbidity, and preventing excessive blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Singh et al reported 7 cases (5 females and 2 males) in 2015. The patients received an ethanol injection via bilateral pedicles under fluoroscopic guidance, followed by posterior decompression and fixation surgery [ 20 ]. The mean age of the participants was 14 years (range: 10–17 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al reported 7 cases (5 females and 2 males) in 2015. The patients received an ethanol injection via bilateral pedicles under fluoroscopic guidance, followed by posterior decompression and fixation surgery [ 20 ]. The mean age of the participants was 14 years (range: 10–17 years).…”
Section: Resultsmentioning
confidence: 99%
“…Curettage could be acceptable because hemangioma is a benign tumor. On the contrary, the results of two case series with surgery indicated that curettage of the tumor is not mandatory [ 19 , 20 ]. During their follow-up periods of 45.3 and 47.6 months, respectively, neither recurrence nor delayed compression fractures were described.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches to effective treatment of these tumors have been more recently developed. 12,18 Although these tumors carry a high risk of bleeding, outcomes of treatment have generally been reported as favorable. 8 In our case, the patient progressively regained neurological function, with the ability to stand on postoperative day 2.…”
Section: Discussionmentioning
confidence: 99%
“…The last option for percutaneous intervention is transarterial embolization of feeding vessels using particulate agents [1]. It has been used as a preoperative adjunct therapy with surgery to reduce blood loss as well as a primary treatment for VHs alone or in conjunction with vertebroplasty [41,[62][63][64]. In a series of 26 patients, Premat et al demonstrated embolization combined with vertebroplasty was safe and effective in treating pain associated with aggressive VHs but was less effective in resolving motor deficits [65].…”
Section: Percutaneous Techniquesmentioning
confidence: 99%
“…In a series of 26 patients, Premat et al demonstrated embolization combined with vertebroplasty was safe and effective in treating pain associated with aggressive VHs but was less effective in resolving motor deficits [65]. The primary role for embolization in the treatment of compressive VHs is preoperative adjunct therapy to reduce the risk of procedural bleeding [62].…”
Section: Percutaneous Techniquesmentioning
confidence: 99%